The effect of cyanoacrylate on knot elongation in three sutures used for prosthetic laryngoplasty in the horse. Issue 3 (24th January 2023) - Watkins, Amanda R.; Ford, Matt; van Eps, Andrew W.; Stefanovski, Darko; Parente, Eric J.
Abstract: Objective: This study investigated the elongation following cyclic loading on square knots of 5 USP multifilament long‐chain ultra‐high molecular weight polyethylene core (UHMWPE), 2 mm woven UHMWPE tape, and 5 USP braided polyester, with and without cyanoacrylate glue. Study design: Experimental study. Sample population: n = 4. Methods: Three conditions (suture without knot, suture with knot, suture with knot + cyanoacrylate) were evaluated for each suture material on a mechanical test stand by measuring the increased length of the construct after cycling from 25 to 50N for 1000 repetitions at 20 mm/second. Knot elongation was determined by subtracting the length of the control suture from the suture with knot or suture with knot + cyanoacrylate. The data were analyzed with a linear regression model with robust estimation of variance. Post‐hoc analysis determined the model adjusted differences (square knot vs. cyanoacrylate) as a difference from control. t ‐tests were conducted to identify the significant findings. Results: Total elongation of polyester (6.2–7.8 mm) was greater than multifilament UHMWPE (3.4–6.4 mm) and UHMWPE tape (2–3.7 mm) for all conditions. Polyester had the lowest knot elongation (1.6 mm) and the addition of cyanoacrylate decreased knot elongation for polyester by 1 mm. Conclusions: Polyester had the most total construct elongation followed by multifilament UHMWPE and UHMWPE tape. Polyester showed the least knot elongation and cyanoacrylate decreased this knot elongation. Clinical significance: Total construct and knot elongation should be considered as contributing factors to loss of arytenoid abduction following prosthetic laryngoplasty when using polyester, multifilament UHMWPE, or UHMWPE tape. Addition of cyanoacrylate to polyester knots should be explored to limit elongation.